Nature's Contributions to Human Health: A Missing Link to Primary Health Care? A Scoping Review of International Overview Reports and Scientific Evidence - Lauwers, Laura; Bastiaens, Hilde; Remmen, Roy; Keune, Hans (Frontiers in Public Health, 2020)
Nature’s contributions to human health (NCH) have gained increased attention internationally in scientific and policy arenas. However, little attention is given to the role of the healthcare sector in this discussion. Primary health care (PHC) is a vital backbone for linking knowledge and practice within the organization of health care. The objective of this scoping review is to evaluate how international overview reports and scientific literature on NCH address to PHC. More specifically, we extracted data on arguments, practice supporting tools and guidelines, challenges and constraints, and management approaches to integrate NCH and PHC. The scientific literature search run in Web of Science. Two independent reviewers screened the scientific publications. Through the scientific literature search we identified 1995 articles of which 79 were eligible for analysis. We complemented the search with a selection of six international overview reports. Both the international overview reports and the scientific publications paid limited attention to the role of PHC regarding NCH. To cope with the current challenges and constraints to integrate NCH and PHC, more evidence on NCH, further development of PHC practice supporting tools, bottom-up integrated approaches, and closer interdisciplinary collaborations are required.